Understanding The Importance and Factors of Participation in The Urban Planning Process: A Case Study of Nigeria - Nwachi, Louis (UI Scholars Hub, 2022)
Studies show that most urban planning systems in many countries still rely on expert-driven, top-down technocratic plan-making processes rather than a public and people-led process. The objective of this paper is twofold: (a) to evaluate the need for public participation in the plan-making process; and (b) to highlight the factors that affect public participation in the plan-making process. A qualitative approach is adapted to obtain these objectives by conducting observations, document studies, and interviews with real-world phenomena. The Metropolitan Area of Abuja, the capital of Nigeria, is examined as the case study. The research finds that public participation and engagement contribute to the plan-making process by identifying the critical urban issues unique to the specific local areas, establishing priorities, and mobilizing resources to meet the identified needs. It also shows that the development of a participation model by city authorities encourages public engagement and helps develop trust between the authorities and various key stakeholder groups. When the public is engaged in developing a particular plan, they become more invested. As they are more inclined to accept, promote and defend it, plan implementation can be enhanced.